Discover answers to your questions with Westonci.ca, the leading Q&A platform that connects you with knowledgeable experts. Join our Q&A platform to get precise answers from experts in diverse fields and enhance your understanding. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.

What is the extraneous solution to the equation [tex]\sqrt{2p+1} + 2\sqrt{p} = 1[/tex]?

A. [tex]p = -4[/tex]
B. [tex]p = -2[/tex]
C. [tex]p = 0[/tex]
D. [tex]p = 4[/tex]


Sagot :

To determine the extraneous solutions to the equation [tex]\(\sqrt{2p + 1} + 2\sqrt{p} = 1\)[/tex], we need to test each of the given values for [tex]\(p\)[/tex] and see if they satisfy the equation. The possible values for [tex]\(p\)[/tex] are [tex]\(-4\)[/tex], [tex]\(-2\)[/tex], [tex]\(0\)[/tex], and [tex]\(4\)[/tex]. Let's evaluate the equation for each of these values:

1. For [tex]\(p = -4\)[/tex]:
- [tex]\(\sqrt{2(-4) + 1} + 2\sqrt{-4}\)[/tex]
- [tex]\(\sqrt{-8 + 1} + 2\sqrt{-4}\)[/tex]
- [tex]\(\sqrt{-7} + 2\sqrt{-4}\)[/tex]

Since [tex]\(\sqrt{-7}\)[/tex] and [tex]\(\sqrt{-4}\)[/tex] involve square roots of negative numbers (which are not real), [tex]\(p = -4\)[/tex] is not a valid solution in the real number domain.

2. For [tex]\(p = -2\)[/tex]:
- [tex]\(\sqrt{2(-2) + 1} + 2\sqrt{-2}\)[/tex]
- [tex]\(\sqrt{-4 + 1} + 2\sqrt{-2}\)[/tex]
- [tex]\(\sqrt{-3} + 2\sqrt{-2}\)[/tex]

Similar to the previous case, [tex]\(\sqrt{-3}\)[/tex] and [tex]\(\sqrt{-2}\)[/tex] are not real numbers, so [tex]\(p = -2\)[/tex] also cannot be a valid solution in the real number domain.

3. For [tex]\(p = 0\)[/tex]:
- [tex]\(\sqrt{2(0) + 1} + 2\sqrt{0}\)[/tex]
- [tex]\(\sqrt{0 + 1} + 2\sqrt{0}\)[/tex]
- [tex]\(\sqrt{1} + 2 \cdot 0\)[/tex]
- [tex]\(1 + 0\)[/tex]
- [tex]\(1\)[/tex]

Here, [tex]\(1 = 1\)[/tex], so [tex]\(p = 0\)[/tex] satisfies the equation.

4. For [tex]\(p = 4\)[/tex]:
- [tex]\(\sqrt{2(4) + 1} + 2\sqrt{4}\)[/tex]
- [tex]\(\sqrt{8 + 1} + 2\sqrt{4}\)[/tex]
- [tex]\(\sqrt{9} + 2 \cdot 2\)[/tex]
- [tex]\(3 + 4\)[/tex]
- [tex]\(7\)[/tex]

Here, [tex]\(7 \neq 1\)[/tex], so [tex]\(p = 4\)[/tex] does not satisfy the equation.

Thus, the values of [tex]\(p\)[/tex] which do not satisfy the equation are the extraneous solutions. These values are:
[tex]\[ p = -4, p = -2, p = 4 \][/tex]

So, the extraneous solutions are [tex]\(-4\)[/tex], [tex]\(-2\)[/tex], and [tex]\(4\)[/tex].